C-Si solar cells formed from spin-on phosphoric acid and boric acid. (August 2015) - Yadav, Akash; Singh, Gajendra; Nekovei, Reza; Jeyakumar, R.
Abstract: This paper reports the fabrication of c-Si based solar cells using spin-on dopants. Solar cells were developed by texturing both surfaces of the c-Si, and forming the p–n junction by spin-coating the n-type dopant followed by rapid thermal processing (RTP). For back surface field formation on the rear side, a similar spin-coating step was undertaken for one cell and e-beam Al deposition for the other. In the case of double-sided spin-coated cell, simultaneous p–n junction and back surface field were formed in one RTP cycle. Without using high performance features in the device, double-sided spin-on doped cell showed Voc of 600 ± 0.01 mV, Jsc of 33.1 ± 0.03 mA/cm 2, FF of 74.26 ± 0.06% and efficiency of 14.74%. As compared to single-sided spin-on doped cell, an improvement in efficiency of about 1.3% has been obtained which can be attributed to boron back surface field. Double-sided spin-on process significantly reduces thermal budget and improves throughput. Besides texturization, high efficiency features have not been used in the device. The results clearly demonstrate that c-Si based solar cells are potentially cost effective to manufacture. Highlights: In one rapid thermal process cycle, low cost cells were fabricated with 14.74% efficiency. Except texturization, high efficiency features (dielectric mirror etc.) have not been used. Emitter and back surface field were formed within 10 min. High efficiency features are normally used to achieve comparable efficiency.